2017
DOI: 10.1111/epi.13702
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to valproic acid as predictor of treatment resistance in genetic generalized epilepsies

Abstract: This study aimed at defining clinical predictors of drug resistance in adults with genetic generalized epilepsy (GGE) who were treated with a broad spectrum of antiepileptic drugs. Of a cohort of 137 unselected adult GGE patients with long-term follow up, clinical and demographic data, putative prognostic factors (e.g., psychiatric comorbidities, electroencephalography [EEG]), treatment response, and data indicative of social status were collected. Fifty-eight patients had seizures within the past year. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 14 publications
(20 reference statements)
2
47
1
4
Order By: Relevance
“…Addition of perampanel led to improvements in seizure outcomes, regardless of concomitant AEDs. Even in patients previously treated with (and presumably failed) valproic acid (which is a strong predictor of refractory seizures in IGE), 43% were free of absence seizures and 54% were free of all seizures at 1 year. Consistent with previous findings with perampanel when added to levetiracetam, the specific concomitant AEDs did not tend to affect the incidence of AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of perampanel led to improvements in seizure outcomes, regardless of concomitant AEDs. Even in patients previously treated with (and presumably failed) valproic acid (which is a strong predictor of refractory seizures in IGE), 43% were free of absence seizures and 54% were free of all seizures at 1 year. Consistent with previous findings with perampanel when added to levetiracetam, the specific concomitant AEDs did not tend to affect the incidence of AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were classified as 'pseudo-resistant', 'drugresistant' and 'non-resistant' as described by Gesche et al [16]. Estimation of incidence and prevalence was based on the entire population on Funen (Data S1).…”
Section: Patient Cohort and Analysesmentioning
confidence: 99%
“…Previous studies have indicated that approximately one-third of patients are non-responsive to VPA (8,9), and the reason for this phenomenon remains elusive. Recently, Gesche et al (10) have demonstrated that resistance to VPA has a specificity of 100% regarding the identification of genetic generalized epileptic patients. Consequently, it is important to elucidate the mechanism underlying VPA efficacy and identify biomarkers predictive of VPA responses.…”
Section: Introductionmentioning
confidence: 99%